Electric machinery and power system fundamentals - Chapman, Stephen J. (Boston : McGraw-Hill, 2002)
Covering the area of machines, this text is designed to be used in a course that combines machinery and power systems into one semester. It focuses on principles and teaches students how to use information as opposed to do a lot of calculations that would rarely be done by a practicing engineer.
1 Mechanical and Electromagnetic Fundamentals 2 Three-Phase Circuits 3 Transformers 4 AC Machinery Fundamentals 5 Synchronous Machines 6 Parallel Operation of Synchronous Generators 7 Induction Motors 8 DC Motors 9 Transmission Lines 10 Power System Representation and Equations 11 Introduction to Power-Flow Studies 12 Symmetrical Faults 13 Unsymmetrical Faults.
Includes bibliographical references and index.
Keywords: Electric machinery; Electric power systems